2023
DOI: 10.3389/fphar.2023.1172908
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin-proteasome system-based signature to predict the prognosis and drug sensitivity of hepatocellular carcinoma

Abstract: Background: Ubiquitin-proteasome system (UPS) is implicated in cancer occurrence and progression. Targeting UPS is emerging as a promising therapeutic target for cancer treatment. Nevertheless, the clinical significance of UPS in hepatocellular carcinoma (HCC) has not been entirely elucidated.Methods: Differentially expressed UPS genes (DEUPS) were screened from LIHC-TCGA datasets. The least absolute shrinkage and selection operator (LASSO) and stepwise multivariate regression analysis were conducted to establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Based on The Cancer Genome Atlas (TCGA) datasets and 961 ubiquitin-proteasome system genes (UPSGs), Liu et al [ 11 ] found that DDB1 and CUL4 associated factor 13 ( DCAF13 ), cell division cycle 20 ( CDC20 ), and proteasome 20S subunit beta 5 ( PSMB5 ) have excellent performance to predict the survival of liver cancer patients. Zhang et al [ 12 ] identified a seven-UPSG prognostic signature, of which autophagy related 10 ( ATG10 ) was found to participate in liver cancer development and prognosis through autophagy, immune response, and tumor metastasis. Therefore, proteasome inhibitors, as a class of potential and effective anti-tumor drugs, have attracted a growing body of attention from researchers.…”
Section: Introductionmentioning
confidence: 99%
“…Based on The Cancer Genome Atlas (TCGA) datasets and 961 ubiquitin-proteasome system genes (UPSGs), Liu et al [ 11 ] found that DDB1 and CUL4 associated factor 13 ( DCAF13 ), cell division cycle 20 ( CDC20 ), and proteasome 20S subunit beta 5 ( PSMB5 ) have excellent performance to predict the survival of liver cancer patients. Zhang et al [ 12 ] identified a seven-UPSG prognostic signature, of which autophagy related 10 ( ATG10 ) was found to participate in liver cancer development and prognosis through autophagy, immune response, and tumor metastasis. Therefore, proteasome inhibitors, as a class of potential and effective anti-tumor drugs, have attracted a growing body of attention from researchers.…”
Section: Introductionmentioning
confidence: 99%